Service Delivery Performance of Urban Local Government in Bangladesh - Jannatul Ferdous; Rajib Chandra Das (Department of Government Studies, Universitas Syiah Kuala, 2022)
Urban local government is critical to the delivery of essential services to residents. Paurashava is one of the tiers of local governments in Bangladesh. But, Paurashava is faced with increasing financial problems. Due to financial restrictions, city governments seem unable to expand much-needed infrastructure and utility services, as well as maintain current facilities at a sufficient level. To enhance urban living standards and alleviate constraints on the national budget, these governments' financial positions must be strengthened. The present study is aimed at exploring the performance management of Paurashava service delivery through utilizing mixed methods. Three Paurashavas were sampled for an in-depth study. The findings of the study reveal that resource mobilization opportunities in Bangladesh's urban areas are limited. A percentage of government grants that are paid based on performance can also be utilized to generate local resources. The major problems are inadequate assessment, inelasticity of revenue, employee training, and poor administration. This paper shows the performance evaluation of the Paurashava by its clients. Thus, this research is helpful to local government policymakers, municipal authorities as policy implementers and service providers, academicians, and those interested in local government and decentralized service delivery systems.